Analisis Pengaruh Strategi Manajemen Operasional terhadap Transportasi - Jasica Asih Hati (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Services or services are services offered to provide more value. By providing excellent service to guests/consumers you will raise the name of a person, a place and even the product itself. The method for writing Literature Review articles is the Library Research and Systematic Literature Review (SLR) method. Systematic Literature Review (SLR) is defined as the process of identifying, assessing and interpreting all available research evidence with the aim of providing answers to research questions in a comprehensive manner. specific. Literature reviews must be used consistently with methodological assumptions. This research is expected to provide in-depth insight into the variables that influence transportation management by understanding the complex relationship between information technology, infrastructure and human resource skills. This research is expected to provide in-depth insight into the variables that influence transportation management by understanding the complex relationship between information technology, infrastructure and human resource skills. In the operational management strategy process, operations managers will carry out four functions, as follows: 1. Planning 2. Organizing 3. Directing 4. Controlling Suggestions for further research, so that it can be more focused on what transportation will be used as an object for operational management.